Digital Labour and Migration Intention: Evidence from Nepalese Youth in the Gig Economy - Singh K., Priti (Brixton Scholarly Review, 2026)
This study aims to examine the relationship between participation in the gig economy and migration intention for Nepalese youth. This study was conducted using a quantitative and cross-sectional method, in which data were collected through questionnaires from 401 respondents aged between 18 and 35 years in Kathmandu, Pokhara, and Chitwan. The migration intention was taken as the dependent variable, while gig income, income stability, payment accessibility, and social prestige were taken as independent variables. SPSS software was used for data analysis, in which all four variables are negatively related with migration intention as per VIF results at 1% significance level. Income stability, gig income, payment accessibility, and social prestige are the top four predicting variables, in that order, as per beta value, which are -0.31, -0.24, -0.19, and -0.17, respectively. The model explained a moderate level of variance for migration intention (R² = 0.24), with the model explaining 24% of the variance in migration intention. What the findings of this study tell us is that lower migration intentions are associated with greater predictability of income, payment systems, and social recognition of gig work. The findings of this study tell us that the gig economy is a ’complementary livelihood pathway’ and not a ’substitute for migration.’ It is not unconditional, with the relationship between such work and migration intention being found in globally connected digital work, and not in locally bounded gig work. This study contributes to migration theory by pointing out the digital pattern of work, which changes conventional migrations in developing economies.